Penarikan Seserahan Pernikahan di Mandailing Natal: Antara Tradisi dan Hukum Islam - Hasibuan, Zuhdi; Asrul Hamid; Raja Ritonga; Andri Muda Nst; Ilham Ramadan Siregar (IAIN PONOROGO, 2025)
This study examines the practice of reclaiming marriage gifts (seserahan) in Mandailing Natal from the perspective of Islamic law and local traditions. Originally intended as a gesture of respect toward women, seserahan has often become a source of post-divorce conflict due to misalignment between customary norms and Sharia principles. Employing a qualitative approach with a descriptive-analytical method, the study integrates literature reviews, in-depth interviews, and participatory observation to explore the social, cultural, and legal dynamics surrounding the practice. The findings reveal that the reclamation of seserahan frequently contradicts the Islamic principle of justice, especially when seserahan is misconstrued as a mahr (dowry) or used to reinforce patriarchal dominance. Moreover, the practice reflects the dilemma faced by modern communities in balancing religious and cultural identities. Proposed solutions include religion-based mediation, Islamic legal education, the revision of customary norms, and a continued research agenda. This research contributes to contemporary Islamic legal discourse by highlighting the need to harmonize local traditions with the universal principles of Islam. The study's outcomes are expected to serve as a foundation for formulating more inclusive and equitable local policies, and to inspire dialogue on how religion and culture can coexist without undermining one another.